AKTIVITAS ENZIM AMILASE JAMUR DARI ISOLAT LEMANG BERAS HITAM (Oryza sativa Siarang) - Annisa, Lara; Fifendy, Mades; Periadnadi, Periadnadi (STKIP PGRI Sumbar, 2013)
ABSTRACK Lemang beras hitam (Oryza sativa Siarang) of Kenagarian Talang Babungo is one of money distinctive Minangkabau foods. Lemang moldy left to get a different taste from the usual lemang. This fungus occurs on chemical procces aided by the amylase enzyme that functions to decompose starch into to units of simple sugars. Research has been performed to determine the activities of fungal amylase enzyme which is isolated from black rice lemang. Researcher was performed in microbiology laboratory of match and science faculty of Andalas Univercity Padang from March from to April in 2013. The researcher used descriptive metode by growing the fungal isolates on rice flour medium (ATB) that aims to identify fungal amylase enzyme which is characterized by the formation of clears areas surrounding the fungal colony. From this research has been successful to rejuvenert the five isolates of the fungus. Amylolitik index is the highest is Penicillium expansum (1,5) and amylolitik index is lowest is Mucor racemosus (0,5).